Analysis of the drivers of Ghana's energy demand change using the Laspeyres index method of decomposition: Q‐effect, I‐effect and S‐effect. (2nd October 2018) - Akrofi, Benjamin; Ackah, Ishmael; Sakyi, Daniel
Abstract: Since independence, Ghana has experienced four major power crises as a result of the low water level in the hydro dams to generate the required amount of power for the country as well as limited and expensive supply of crude oil and gas. These energy supply constraints make it imperative for the country to rely on demand‐side management policies to address the energy crisis of the country. However, demand‐side management policies that are applied in generic terms without knowing the exact cause are likely to fail. This study therefore decomposes the factors that influence energy consumption into activity effect, intensity effect and structural effect, so that policymakers will know which factor(s) and also the sectors of the economy that are responsible for the large increases in energy consumption. This way, policymakers will apply the appropriate demand‐side management policy to a particular factor(s) and the sectors causing the increase to get the desired results. The study finds that activity effect is the main driver of energy consumption in Ghana.